Analisis Reduksi Polutan Kromium (Cr) Menggunakan Agen Fitoremediasi Mangrove di Ekosistem Pesisir Tulehu Ambon Provinsi Maluku - Asyik, Asyik Nur Allifah AF (Biotropic : The Journal of Tropical Biology, 2026)
Mangroves are aquatic vegetation that act as phytoremediation agents due to their ability as biofilters, adsorbing, and accumulating pollutants in the environment, thus contributing to improving water quality. The detoxification mechanism of chromium pollutants carried out by mangroves is a cost-effective solution in addressing coastal environmental pollution. The research target focused on assessing the reduction capacity of mangroves against chromium pollutants in the coastal ecosystem of Tulehu Ambon, Maluku Province. This study was conducted for two months, from mid-Juny to mid-July 2025. Sampling of chromium pollutants found in mangrove roots, leaves, and sediments was carried out at three observation stations based on location characteristics. Chromium analysis was determined from the results of the Atomic Absorption Spectrophotometer (AAS) display. This study revealed that mangroves have the potential to reduce pollutants through deposition and stabilization processes, as indicated by FTD values ​​> 1, which indicate their role in phytostabilization mechanisms. The preservation and protection of mangrove forests must be a serious concern for the sustainability of coastal ecosystems in this area.